Produção de biomassa, teor de óleo essencial e trocas gasosas em Aloysia triphylla submetida a diferentes disponibilidades hídricas - Schwerz, Luciano (2013)
The increasing demand for drugs in Brazil brings us to the improvement in cultivation of medicinal plants, that amount plus the quality is recommended. This study aimed to evaluate the growth, development, essential oil production as well as gas exchange and physiological parameters in Aloysia triphylla under different water availability throughout the four seasons. The experiment was conducted in greenhouse belonging to the agroclimatology laboratory of the UFSM campus of Frederico Westphalen - RS, in a randomized complete block design with four replications. Evaluations were made on the day that marked the half of each season (summer, autumn, winter and spring), and all plant material collected 20 cm above ground. The water availability (DH) was based on the reference evapotranspiration to the external environment being applied 125, 100, 75 and 50% of ETo in an irrigation interval of two days, totaling a blade 1620.06, 1304.05; 988 , 03 and 672.02 mm. year-1, respectively. The production of biomass, height and indirect measurement of chlorophyll (SPAD) had linear and cubic responses to water availability, being negative to reduce it. The effect of seasonality reveals that the spring season has growth and biomass production stronger, surpassing all other stations, while the winter was responsible for lower growth and production. The essential oil content was positively affected by water availability, being the depth of the highest yield of 75 and 50% of ETo respectively. The seasons summer and winter detained the highest content of essential oil in the leaves. And the variables which comprise plant gas exchange with the atmosphere, perspiration was lower due to the reduction of DH, thus promoting a greater stomatal resistance and increased temperature of the sheet, and the abaxial responsible for most of the total transpiration plant.